2020
DOI: 10.1016/j.anbehav.2020.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Beyond thermal melanism: association of wing melanization with fitness and flight behaviour in a butterfly

Abstract: Cold developmental conditions can greatly affect adult life history of ectotherms in seasonal habitats. Such effects are mostly negative, but sometimes adaptive. Here, we tested how cold conditions experienced during pupal development affect adult wing melanization of an insect ectotherm, the Glanville fritillary butterfly, Melitaea cinxia . We also assessed how in turn previous cold exposure and increased melanization can shape adult behaviour and fitness, by monitoring individuals in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 79 publications
0
7
1
Order By: Relevance
“…In particular, oceanic birds seem to exploit the lift-to-drag ratio increases for heated wings. Since colour can have a significant impact on flight performance, often linked with individual quality [55,56], our findings that darker, more-melanized wings improve flight efficiency can have far-reaching implications for studies on individual quality (i.e. fitness).…”
Section: Resultsmentioning
confidence: 96%
“…In particular, oceanic birds seem to exploit the lift-to-drag ratio increases for heated wings. Since colour can have a significant impact on flight performance, often linked with individual quality [55,56], our findings that darker, more-melanized wings improve flight efficiency can have far-reaching implications for studies on individual quality (i.e. fitness).…”
Section: Resultsmentioning
confidence: 96%
“…A commendable exception is the work of Jarvi et al ( 2019 ), who were able to show by infrared imaging that red‐colored imagines of Junonia coenia , which appear in autumn, warm up faster and more strongly than tan individuals of summer. However, the actual thermobiological relevance of darker coloration of butterfly wings for ecophysiological performance remains unclear, since Rosa and Saastamoinen ( 2020 ) found that thermobiological behavior (“wing vibrating” preceding flight) in Melitaea cinxia was not dependent on pigmentation intensity. On the contrary, heavily pigmented individuals were more mobile in this study, which could well have had thermobiological causes.…”
Section: Discussionmentioning
confidence: 99%
“…Additional and sex‐specific advantages of more melanistic forms at high altitudes were shown for Colias species by Ellers and Boggs ( 2004 ). In other habitats, however, stronger melanization could cause fitness costs and reduced mating success (Hofmann & Tremewan, 2017 ; Kettlewell, 1973 ; Rosa & Saastamoinen, 2020 ), which plausibly could contribute to stabilizing selection of moderately pigmented individuals in temperate climates. Interestingly, Heinrich ( 1986 ) could show in a high‐mountain habitat that thermoregulation is also strongly correlated with butterfly thorax size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there is evidence in the literature for both Gloger's and Bogert's (Ribot et al 2019, Goldenberg et al 2021), but those studies focus on a few or a group of closely related species, which were likely shaped by similar eco‐evolutionary pressures and dynamics. However, if the number of focal taxa changes or different focal species are selected, then often no patterns are found (Forsman 2011, Rosa and Saastamoinen 2020). Finally, dark colouration may be a pleiotropic effect of genes involved in the melanocortin system, of which melanin production is only a part of, and therefore the integument darkness might be a side‐product of selection on other specific traits (Ducrest et al 2008, Baeckens and Van Damme 2018).…”
Section: Inconsistences Between Coloration and Body Size Rulesmentioning
confidence: 99%